2011
DOI: 10.1159/000316966
|View full text |Cite
|
Sign up to set email alerts
|

Beyond DSM-IV Bereavement Exclusion Criterion E for Major Depressive Disorder

Abstract: ticle, we propose to revise DSM-IV bereavement exclusion and keep the V code for bereavement as suggested by Paula Clayton [19] . In addition, in the event that criterion E is deleted, we believe that criterion A for major depression should be revised to require at least 7 of the 9 criterion A inclusion symptoms for MDE in all types of MDD, which would satisfy the concerns raised by Lichtenberg and Belmaker [3] and Bech [4] about the overinclusiveness of criterion A, leading to overdiagnosis of MDE. Adjusting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…If the loss of pleasure and interest becomes very severe and pervasive, demoralization can follow 37 . Therefore, demoralization in major depressive patients may represent a psychological response to a prolonged and severe loss of interest and pleasure 48 . However, in other medically ill patients the relationship between major depression and demoralization might be characterized by a different sequence.…”
Section: Discussionmentioning
confidence: 99%
“…If the loss of pleasure and interest becomes very severe and pervasive, demoralization can follow 37 . Therefore, demoralization in major depressive patients may represent a psychological response to a prolonged and severe loss of interest and pleasure 48 . However, in other medically ill patients the relationship between major depression and demoralization might be characterized by a different sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, additional practical proposals have been offered that largely sidestep the issue of consideration of stressful life event context in assessment of MDD while still addressing the potential issue of overdiagnosis should the bereavement exclusion criterion be removed. For example, Chouinard and colleagues 14 proposed that the exclusion should be removed, but the criteria should be revised to require at least 7 out of 9 symptoms instead of the current 5 out of 9. To increase overall diagnostic accuracy, Gopal and Bursztajn 42 more broadly recommend a complete reformatting of the DSM system to integrate symptom weights, narrative descriptions, and dimensional scales with the “checklist” rule-based style of the current DSM (e.g., “x symptoms out of y”), although such proposals would remain to be systematically tested against the current system.…”
Section: Discussionmentioning
confidence: 99%
“…The first camp proposes that the bereavement exclusion criterion should be removed completely from the manual, so that MDD is diagnosed more purely with respect to the presence of current symptoms, marked distress, and impairment. 9,10,1416 The justifications in the literature for this change are complex and encompass a range of views, but one key justification is that once the threshold for disordered symptoms, as defined by the DSM , is met, it indicates that a breakdown in functioning has occurred. From this perspective, there is no need to assess the behaviors with reference to life event context because the behaviors in and of themselves reflect dysfunction and suffering and thereby warrant clinical attention.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the MDD threshold should be raised to seven symptoms from the current five “to lower the risk of ‘over‐diagnosis’ or pathologizing ‘normal’ depression or sadness” . This proposal is supported by findings over the years suggesting a discontinuity between MDD episodes with five to six and seven to nine symptoms .…”
Section: Methodsmentioning
confidence: 99%